Preparation method of oxide solid electrolyte

By applying water-soluble polymer material glue to form a protective layer on the inner wall of the high-temperature reactor, the problem of sticking and expansion of oxide solid electrolyte in the preparation of high-temperature solid phase is solved, and the product yield and utilization of reaction vessels are improved. The production rate of electrolytes is achieved.

CN119297377APending Publication Date: 2025-01-10HEBEI GUANGXING SEMICON TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411254740.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

During the preparation of oxide solid electrolytes in high-temperature solid phase, the product is prone to stick to walls and expands, resulting in low product yield and low reuse rate of reaction vessels.

Method used

Coated glue of water-soluble polymer material to form a protective layer on the inner wall of the high-temperature reactor, containing only C, H and O elements, avoiding sticking walls and expansion, and ensuring humidity in the reaction vessel, ensuring easy removal and post-treatment of the product.

Benefits of technology

It improves the yield of oxide solid electrolyte and the utilization rate of reaction vessels, ensures the electrochemical performance and safety of the product, and is suitable for large-scale commercial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297377A_ABST
    Figure CN119297377A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of an oxide solid electrolyte, which comprises the following steps: coating a glue solution on the inner wall of a high-temperature reactor to form a protective layer; the glue solution is an aqueous solution of a water-soluble polymer material; the high polymer material only contains three elements of C, H and O; putting the precursor powder of the oxide solid electrolyte into a high-temperature reactor containing a protective layer, raising the temperature to a calcination temperature, and keeping the temperature at the calcination temperature so as to enable the precursor powder of the oxide solid electrolyte to react; and after the reaction is finished, cooling to obtain the oxide solid electrolyte. The technical problem to be solved by the invention is how to provide the preparation method of the oxide solid electrolyte, so that the phenomena of wall adhesion and expansion can be avoided when the oxide solid electrolyte is prepared by a high-temperature solid-phase method, and the preparation method has the advantages of simple preparation process, good size uniformity and high yield of the high-temperature solid-phase method; and the yield of oxide solid electrolyte products can be improved, and the utilization rate of the reaction container is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a method for preparing an oxide solid electrolyte. Background Art

[0002] As an energy storage device, lithium-ion batteries have the advantages of high energy density, light weight, no memory effect, low self-discharge efficiency and long cycle life. They have been widely used in consumer electronic products. Their market has gradually expanded in recent years to meet the demand for high-energy-density portable power sources for products such as electric vehicles, drones, robots and various smart devices.

[0003] Currently, commercial lithium-ion batteries mainly use liquid electrolytes. Although the organic solvents they contain have strong ionic conductivity, they are volatile and flammable, which leads to greater safety hazards. The biggest advantage of solid-state batteries using solid electrolytes is that they are non-flammable and have high strength, which can prevent lithium dendrites from piercing and can match lithium metal negative electrodes with higher energy density. Therefore, the possibility of combustion is eliminated from the root, and it is highly safe.

[0004] Solid electrolytes are mainly divided into polymer electrolytes, sulfide electrolytes and oxide electrolytes, among which oxide electrolytes have high ionic conductivity, high chemical stability and excellent comprehensive performance, and have received extensive attention. Oxide solid electrolytes can be synthesized by high temperature solid phase method, which has the advantages of simple preparation process, good size uniformity and high yield. However, during high temperature calcination, the product often expands and sticks to the wall, causing the material to stick to the wall, making it difficult to take out the target product, and it is inconvenient to post-process it, thus resulting in low yield of the product, and low reuse rate of the reaction vessel. Therefore, how to prepare oxide solid electrolytes by high temperature solid phase method so that they are not sticky and do not expand is a technical problem that needs to be solved in this field.

[0005] Literature reports that adding organic additives to the raw materials can improve the fluidity and moisture retention of the materials, and prevent the materials from sticking to the inner wall of the crucible during calcination. However, although organic additives can be decomposed and volatilized during high-temperature calcination without generating ion pollution, the presence of organic additives changes the composition ratio of the reactants, and introduces a small amount of impurities into the final product, thus affecting the performance of the target product. Summary of the invention

[0006] A technical problem to be solved by the present invention is how to provide a method for preparing an oxide solid electrolyte so that when the oxide solid electrolyte is prepared by a high-temperature solid phase method, wall sticking and expansion phenomena will not occur. The method has the advantages of a simple preparation process, good size uniformity and high yield of the high-temperature solid phase method, and can also improve the yield of the oxide solid electrolyte product and the utilization rate of the reaction container.

[0007] In order to solve the above technical problems, an embodiment of the present invention provides a method for preparing an oxide solid electrolyte, which comprises the following steps:

[0008] 1) Applying glue on the inner wall of the high-temperature reactor to form a protective layer; the glue is an aqueous solution of a water-soluble polymer material; the polymer material contains only three elements: C, H and O;

[0009] 2) Putting the precursor powder of the oxide solid electrolyte into a high-temperature reactor containing a protective layer, heating it to a calcination temperature, and keeping it warm at the calcination temperature to allow the precursor powder of the oxide solid electrolyte to react; cooling it after the reaction is completed to obtain an oxide solid electrolyte.

[0010] In some embodiments, the polymer material is selected from at least one of polyethylene oxide, polyethylene glycol, polyvinyl alcohol and starch.

[0011] In some embodiments, the viscosity of the glue is 500-10000 mPa.s. In some embodiments, the glue is prepared according to the following steps: adding the polymer material into water, stirring to completely dissolve it, and obtaining the glue; wherein, in terms of mass percentage, the glue comprises 1-20% of the polymer material and 80-99% of water; the sum of the mass percentages of the polymer material and the water is 100%.

[0012] In some embodiments, the protective layer has a thickness of 0.5 to 5 mm.

[0013] In some embodiments, the oxide solid electrolyte is a garnet-type structure, a NASICON-type solid electrolyte, or a perovskite-type solid electrolyte.

[0014] In some embodiments, the high temperature reactor is an alumina crucible or a zirconia crucible.

[0015] In some embodiments, the heating rate of the heating is 1 to 5° C. / min.

[0016] In some embodiments, the calcination temperature is 500-1200°C.

[0017] In some embodiments, the insulation time is 2 to 48 hours.

[0018] Through the above technical scheme, the preparation method of the oxide solid electrolyte proposed by the present invention is that a water-soluble organic polymer material containing only three elements of C, H and O is dissolved in water to completely dissolve it to form a glue with a certain viscosity, and then the obtained glue is coated on the inner surface of a high-temperature reaction container to form a protective layer inside the reaction container; then, the mixed oxide solid electrolyte precursor powder is put into the reaction container according to the high-temperature solid phase method, and the temperature is increased to the calcination temperature at a certain heating rate, and then the temperature is kept at the calcination temperature for a period of time to allow the oxide solid electrolyte precursor powder to fully react; after the reaction is completed, it is cooled naturally to obtain the target oxide solid electrolyte; the technical scheme of the present invention has the following advantages: first, the use of water-soluble organic polymer material The molecular material is coated on the inner wall of the reaction container, which contains no volatile flammable substances and is highly safe. Secondly, the water-soluble organic polymer material contains only three elements, namely carbon (C), hydrogen (H) and oxygen (O), which can decompose and volatilize under high temperature conditions without residue, so it will not affect the composition of the final product. Thirdly, the water-soluble polymer material is coated on the inner surface of the reaction container in advance before the reaction raw materials are added, which has no effect on the ingredients of the oxide solid electrolyte precursor powder, will not change the material ratio of the oxide solid electrolyte precursor powder, and will not introduce impurities. Fourthly, the product oxide solid electrolyte obtained after the reaction does not expand or stick to the wall, and is very easy to take out, which is very convenient for post-processing the reaction product, can improve the product yield, is conducive to large-scale commercial production, and has high commercial value.

[0019] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Example 1 Photo of the crucible after the calcination was completed and the reaction product was taken out

[0021] Figure 2 Comparative Example 1: Photo of the crucible after the reaction product was taken out after calcination DETAILED DESCRIPTION

[0022] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined purpose of the invention, the following is a detailed description of the preparation method of an oxide solid electrolyte proposed in accordance with the present invention, its specific implementation method, structure, characteristics and effects, in combination with the preferred embodiments.

[0023] The present invention provides a method for preparing an oxide solid electrolyte, which comprises the following steps: first, preparing a glue liquid of a water-soluble polymer material; second, coating the inner wall of a reaction container with the prepared glue liquid so as to form a protective layer inside the reaction container; and finally, preparing ingredients of a precursor powder of the oxide solid electrolyte, mixing the ingredients evenly, and then putting them into a reaction container coated with the glue liquid for high-temperature calcination to obtain the oxide solid electrolyte.

[0024] The technical solution of the present invention is an improvement on the method for preparing oxide solid electrolyte by high-temperature solid phase method in the prior art. It only makes temporary changes to the reaction container. Before high-temperature calcination to prepare oxide solid electrolyte, the inner wall of the reaction container is coated with the glue of the present invention to form a protective layer. The glue coated on the inner wall of the reaction container is gradually decomposed. Since the glue of the present invention contains only three elements of C, H and O, the products of water and carbon dioxide formed during the decomposition of the glue volatilize, so the products of the decomposition of the glue will not form residues in the target product oxide solid electrolyte, so it has no effect on the electrochemical properties of the target product. Moreover, since the protective layer is gradually decomposed to form volatile products during the high-temperature calcination process, after the reaction is completed, there are few residual substances in the reaction container, which improves the reuse rate of the reaction container. Further, during the high-temperature calcination process, the protective layer separates the reaction raw materials and reaction products from the inner wall of the container, thereby avoiding the reaction raw materials and reaction products from sticking to the wall, and since the decomposition products of the glue contain water components, the humidity of the reaction raw materials and products can be increased, thereby effectively alleviating the problem of material expansion caused by gas discharge during the high-temperature calcination process to prepare the electrolyte, thereby improving the yield of the prepared solid electrolyte.

[0025] The yield rate of the present invention = the quality of the finished product obtained from the crucible with qualified quality / the theoretical quality of the finished product.

[0026] The qualified quality mentioned in the present invention means that the reaction product has no swelling in appearance and the electrochemical properties are not affected.

[0027] The high temperature reaction vessel is preferably an alumina crucible or a zirconia crucible.

[0028] The oxide solid electrolyte may be a garnet structure, a NASICON solid electrolyte, or a perovskite solid electrolyte. The specific ratio of the oxide solid electrolyte precursor powder may be implemented according to the conventional ratio in the prior art, and the present invention does not make any specific limitation.

[0029] Preferably, the oxide solid electrolyte has a garnet structure.

[0030] In some embodiments, when the oxide solid electrolyte is Li7La3Zr2O 12(LLZO), its precursor powders are Li2CO3, La2O3, and ZrO2, and the molar ratio is Li2CO3:La2O3:ZrO2=7:3:4. The types and proportions of the materials can be adjusted according to actual needs.

[0031] The key steps in the technical solution of the present invention are the preparation and coating of the glue. In order to avoid the influence of the protective layer on the calcination reaction, the water-soluble organic polymer material for preparing the glue of the present invention is limited to only three elements, C, H and O, which can be decomposed and volatilized during the calcination process; the organic polymer material is preferably at least one of polyethylene oxide, polyethylene glycol, polyvinyl alcohol and starch.

[0032] The viscosity of the glue liquid prepared in the present invention is preferably 500 to 10000 mPa.s. When the viscosity is too low, it is difficult for the glue liquid to form a wall on the inner wall of the reaction container, resulting in the glue liquid being almost unable to form a protective layer, or even if a protective layer is formed, its thickness is relatively thin, and it is difficult to achieve the technical effect of the present invention; however, the higher the viscosity of the glue liquid, the better; when the viscosity of the glue liquid is too high, due to the strong cohesion force inside the glue liquid, it is difficult for the glue liquid to spread on the inner wall of the reaction container, resulting in difficulty in applying the glue liquid, affecting the uniformity of the protective layer formed inside the reaction container, and even causing the glue liquid to be unable to be applied.

[0033] In addition, the viscosity of the glue also has a great influence on the thickness of the coating; generally, when the viscosity of the glue is low, the protective layer of a single coating is thinner; in order to obtain a protective layer of appropriate thickness, multiple coatings may be required, which is inefficient; and when the viscosity of the glue is high, the protective layer of a single coating is thicker and the uniformity of the coating is poor, which affects the heat transfer and uniformity of the reaction raw materials during the high-temperature calcination process, and thus affects the performance of the subsequent high-temperature calcination products.

[0034] In order to ensure that no wall adhesion and expansion occur when preparing oxide solid electrolytes by high-temperature solid phase method, the thickness of the protective layer coated on the inner wall of the reaction vessel needs to be controlled. If the thickness of the protective layer is too thin, it may fail to protect against wall adhesion and expansion due to uneven local coating of the protective layer; and if the thickness of the protective layer is too thick, under the premise that it can ensure the protective effect, the excess thickness may increase the cost of the protective layer, but fail to produce better effects, resulting in cost waste, uneconomical, and difficult to remove; the preferred thickness of the protective layer of the present invention is 0.5 to 5 mm.

[0035] Since the process of preparing the glue solution of the present invention is to add the water-soluble organic polymer material directly to water under stirring at room temperature (25±1°C), stir to dissolve the polymer material, and form a uniform glue solution, that is, no thickener or other auxiliary agent is used to adjust the viscosity of the glue solution during the preparation of the glue solution, therefore, the viscosity of the glue solution prepared by the present invention is directly related to the mass of the solute in the glue solution, so that the present invention can control the final viscosity index of the glue solution by controlling the ratio of materials in the preparation process of the glue solution. Since the greater the mass percentage of the polymer material in the glue solution, the higher the viscosity of the glue solution. In some embodiments, the organic polymer material used in the present invention is polyethylene oxide. In order to ensure the viscosity of the prepared glue solution, the glue solution preferably includes 1 to 20% of the polymer material and 80 to 99% of water in terms of mass percentage, wherein the sum of the mass percentage of the polymer material and the water is 100%.

[0036] In addition, since no other additives are added during the preparation of the colloid according to the present invention, the polymer material is prone to agglomeration and flocculation when in contact with water, thereby affecting the quality of the colloid. Therefore, when using the preparation method of the present invention, it is necessary to pay attention to properly adjusting the stirring speed to match the speed at which the polymer material is added to the water, thereby avoiding agglomeration and flocculation of the polymer material in the water.

[0037] The present invention can feed the raw materials of the oxide solid electrolyte after the protective layer is formed in the reaction container. First, the precursor powder of the oxide solid electrolyte is weighed according to the needs of the target product, and various raw materials are mixed evenly; then the evenly mixed mixture powder is put into the reaction container coated with glue; then the temperature is raised to the calcination temperature, and the temperature is kept at the calcination temperature to allow the precursor powder of the oxide solid electrolyte to react; after the reaction is completed, the temperature is naturally cooled to obtain the oxide solid electrolyte.

[0038] The present invention controls the heating rate to be 1 to 5°C / min, and preferably, the heating rate is 3 to 5°C / min. When the heating rate is too slow, on the one hand, the raw materials in the reaction vessel are heated slowly, which reduces the production efficiency, and on the other hand, it is not conducive to the smooth volatilization of the products formed by the decomposition of the colloidal solution in the reaction vessel, thereby affecting the quality and performance of the prepared oxide solid electrolyte; when the heating rate is too fast, the inside of the reaction vessel is heated unevenly, on the one hand, the reaction of the electrolyte raw materials inside the reaction vessel will be affected, and on the other hand, the protective layer formed by the glue applied to the inner wall of the reaction vessel is heated unevenly, and then the decomposition and distribution of the glue on the surface of the protective layer are uneven, so that the various parts of the glue protective layer are subjected to uneven force, and then the glue may fall off, so that the protective effect of the protective layer is reduced or even has no protective effect.

[0039] The calcination temperature can be adjusted according to the type of target product, and it has a certain influence on the formation of the oxide solid electrolyte. Too high or too low calcination temperature is not conducive to the formation of the target oxide solid electrolyte. In order to ensure the formation of the oxide solid electrolyte, the preferred calcination temperature of the present invention is 500-1200°C.

[0040] The calcination time will be adjusted according to the different oxide solid electrolytes and the different calcination temperatures. In order to shorten the production cycle and reduce production energy consumption, the preferred insulation time of the present invention is 2 to 48 hours at a suitable calcination temperature.

[0041] As can be seen from the above, the technical solution of the present invention forms a protective layer inside the reaction container by spreading the water-soluble glue containing only three elements of C, H and O all over the inner surface of the high-temperature reaction container, which can effectively avoid wall sticking and expansion during the production process, thereby avoiding the problem that the target product is difficult to take out for post-processing, improving the yield of the target product, and also improving the reuse rate of the reaction container; at the same time, the present invention strictly limits the components of the glue, so that it will neither participate in the calcination reaction nor have any residue in the target product, and will not affect the material ratio of the oxide solid electrolyte, and has a very good technical effect.

[0042] The present invention will be further described below in conjunction with specific embodiments, but this should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.

[0043] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods well known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the common meanings understood by ordinary technicians in the field to which the present invention belongs.

[0044] Embodiment 1:

[0045] In this embodiment, an alumina crucible coated with polyethylene oxide glue is used to prepare the oxide solid electrolyte Li 1.3 Al 0.3 Ti 1.7 (PO4)3. The specific steps are as follows:

[0046] 1) Adding polyethylene oxide to water under stirring conditions, the formed glue solution is shown in Appendix 1: the mass percentage of polyethylene oxide in the glue solution is 10%, and the viscosity of the glue solution is 5000 mPa.s;

[0047] 2) The glue prepared in this example was applied to the inner surface of the alumina crucible, as shown in Table 1, and the thickness of the glue coating was controlled to be 1 mm.

[0048] 3) Weigh Li2CO3, Al2O3, TiO2, NH4H2PO4 powders according to the molar ratio of Li2CO3: Al2O3: TiO2: NH4H2PO4 = 1.3: 0.3: 3.4: 6, and mix them evenly. Pour the evenly mixed mixture into the above-mentioned alumina crucible coated with glue; then, place the crucible in a high-temperature furnace for calcination. The calcination process is shown in Table 1: that is, increase the temperature to 900°C at a rate of 5°C / min, keep warm for 6 hours; then cool to room temperature; finally, take out the reaction product from the crucible to obtain the final product.

[0049] The ionic conductivity of the reaction product is detected. The specific detection method is as follows:

[0050] Ionic conductivity test:

[0051] The ionic conductivity of the solid electrolyte is obtained by assembling a blocking electrode and performing an electrochemical impedance spectroscopy (EIS) test. The specific operation method is as follows:

[0052] The composite oxide solid electrolyte sheet prepared in this embodiment has stainless steel sheets as blocking electrodes on both sides to form a symmetrical battery; the electrochemical workstation used is DH7001, and the frequency range is 0.01~10 6 Hz, test the EIS of oxide solid electrolyte sheets at 25°C. The ionic conductivity of the solid electrolyte is calculated as follows:

[0053] δ=L / (R·S)

[0054] Where, δ is the ionic conductivity (unit S / cm), L is the thickness of the solid electrolyte sheet (unit cm), R is the intrinsic resistance of the solid electrolyte (unit Ω), S is the effective cross-sectional area of ​​the solid electrolyte sheet (unit cm 2 ). The higher the test result of ionic conductivity, the better the ionic conductivity. The test results are shown in Table 2.

[0055] The photo of the crucible obtained after the reaction product was taken out is shown in the attached figure. Figure 1 As shown in the attached Figure 1 As can be seen, there is no product residue on the inner wall of the crucible.

[0056] The oxide solid electrolyte Li obtained in this example 1.3 Al 0.3 Ti 1.7 The yield and appearance status of (PO4)3 are summarized in Table 2.

[0057] Example 2

[0058] In this embodiment, an alumina crucible coated with polyethylene oxide glue is used to prepare the oxide solid electrolyte Li 1.3 Al 0.3 Ti 1.7 (PO4) 3. The specific operation steps are the same as those in Example 1, and the difference from Example 1 is that the relevant process parameters are different. The specific process parameters are shown in Table 1.

[0059] The oxide solid electrolyte Li obtained in this example 1.3 Al 0.3 Ti 1.7 The ion conductivity of (PO4)3 was tested by the same method as in Example 1, and the test results are respectively summarized in Table 2.

[0060] The oxide solid electrolyte Li obtained in this example 1.3 Al 0.3 Ti 1.7 The yield and appearance status of (PO4)3 are summarized in Table 2.

[0061] Example 3

[0062] In this embodiment, an alumina crucible coated with polyethylene oxide glue is used to prepare the oxide solid electrolyte Li 1.3 Al 0.3 Ti 1.7 (PO4) 3. The specific operation steps are the same as those in Example 1, and the difference from Example 1 is that the relevant process parameters are different. The specific process parameters are shown in Table 1.

[0063] The oxide solid electrolyte Li obtained in this example 1.3 Al 0.3 Ti 1.7 The ion conductivity of (PO4)3 was tested by the same method as in Example 1, and the test results are respectively summarized in Table 2.

[0064] The oxide solid electrolyte Li obtained in this example 1.3 Al 0.3 Ti 1.7 The yield and appearance status of (PO4)3 are summarized in Table 2.

[0065] Example 4

[0066] In this embodiment, a zirconia crucible coated with polyethylene glycol glue is used to prepare the oxide solid electrolyte Li 1.3 Al 0.3 Ti 1.7(PO4)3. The specific operation steps and process parameters are basically the same as those in Example 1, and the difference from Example 1 is that the concentration and viscosity of the glue solution in this example are different, and the heating rate during the high-temperature calcination process is 3°C / min. The specific process parameters are shown in Table 1.

[0067] The oxide solid electrolyte Li obtained in this example 1.3 Al 0.3 Ti 1.7 The ion conductivity of (PO4)3 was tested by the same method as in Example 1, and the test results are respectively summarized in Table 2.

[0068] The oxide solid electrolyte Li obtained in this example 1.3 Al 0.3 Ti 1.7 The yield and appearance status of (PO4)3 are summarized in Table 2.

[0069] Example 5

[0070] In this embodiment, an alumina crucible coated with polyvinyl alcohol glue is used to prepare the oxide solid electrolyte Li 1.3 Al 0.3 Ti 1.7 (PO4)3. The specific operation steps and process parameters are basically the same as those in Example 1, and the difference from Example 1 is that the concentration and viscosity of the glue solution in this example are different, and the heating rate during the high-temperature calcination process is 1°C / min. The specific process parameters are shown in Table 1.

[0071] The oxide solid electrolyte Li obtained in this example 1.3 Al 0.3 Ti 1.7 The ion conductivity of (PO4)3 was tested by the same method as in Example 1, and the test results are respectively summarized in Table 2.

[0072] The oxide solid electrolyte Li obtained in this example 1.3 Al 0.3 Ti 1.7 The yield and appearance status of (PO4)3 are summarized in Table 2.

[0073] Example 6

[0074] In this embodiment, an alumina crucible coated with starch glue is used to prepare the oxide solid electrolyte Li 1.3 Al 0.3 Ti 1.7 (PO4)3. The specific operation steps and process parameters are basically the same as those in Example 1, except that the concentration and viscosity of the glue solution in this embodiment are different, and the thickness of the glue solution applied to the reaction container is 5.5 mm. The specific process parameters are shown in Table 1.

[0075] The oxide solid electrolyte Li obtained in this example 1.3 Al 0.3 Ti 1.7 The ion conductivity of (PO4)3 was tested by the same method as in Example 1, and the test results are respectively summarized in Table 2.

[0076] The oxide solid electrolyte Li obtained in this example 1.3 Al 0.3 Ti 1.7 The yield and appearance status of (PO4)3 are summarized in Table 2.

[0077] Example 7

[0078] In this embodiment, an alumina crucible coated with polyethylene oxide glue is used to prepare the oxide solid electrolyte Li 1.3 Al 0.3 Ti 1.7 (PO4)3. The specific operation steps and process parameters are basically the same as those in Example 1, except that the mass percentage of polyethylene oxide in the glue prepared in this example is 25%, and the thickness of the glue applied to the reaction container is 6.0 mm. The specific process parameters are shown in Table 1.

[0079] The oxide solid electrolyte Li obtained in this example 1.3 Al 0.3 Ti 1.7 The ion conductivity of (PO4)3 was tested by the same method as in Example 1, and the test results are respectively summarized in Table 2.

[0080] The oxide solid electrolyte Li obtained in this example 1.3 Al 0.3 Ti 1.7 The yield and appearance status of (PO4)3 are summarized in Table 2.

[0081] Example 8

[0082] In this embodiment, an alumina crucible coated with polyethylene oxide glue is used to prepare the oxide solid electrolyte Li 1.3 Al 0.3 Ti 1.7 (PO4)3. The specific operation steps and process parameters are basically the same as those in Example 1, except that the heating rate in the high-temperature calcination process in this example is 6°C / min. The specific process parameters are shown in Table 1.

[0083] The oxide solid electrolyte Li obtained in this example 1.3 Al 0.3 Ti 1.7The ion conductivity of (PO4)3 was tested by the same method as in Example 1, and the test results are respectively summarized in Table 2.

[0084] The oxide solid electrolyte Li obtained in this example 1.3 Al 0.3 Ti 1.7 The yield and appearance status of (PO4)3 are summarized in Table 2.

[0085] Example 9

[0086] In this embodiment, an alumina crucible coated with polyethylene oxide glue is used to prepare the oxide solid electrolyte Li 1.3 Al 0.3 Ti 1.7 (PO4)3. The specific operation steps and process parameters are basically the same as those in Example 1, except that the heating rate in the high-temperature calcination process in this example is 0.5°C / min. The specific process parameters are shown in Table 1.

[0087] The oxide solid electrolyte Li obtained in this example 1.3 Al 0.3 Ti 1.7 The ion conductivity of (PO4)3 was tested by the same method as in Example 1, and the test results are respectively summarized in Table 2.

[0088] The oxide solid electrolyte Li obtained in this example 1.3 Al 0.3 Ti 1.7 The yield and appearance status of (PO4)3 are summarized in Table 2.

[0089] The process-related parameters involved in the process of preparing the oxide solid electrolyte sheet in the embodiment of the present invention are shown in Table 1.

[0090] Comparative Example 1

[0091] In this comparative example, an alumina crucible without glue was used to prepare Li 1.3 Al 0.3 Ti 1.7 (PO4)3 oxide solid electrolyte. Except that the reaction container is not coated with glue solution, the other steps are exactly the same as those in Example 1. The specific process parameters are shown in Table 1.

[0092] The oxide solid electrolyte Li obtained in this comparative example 1.3 Al 0.3 Ti 1.7 The ion conductivity of (PO4)3 was tested by the same method as in Example 1, and the test results are respectively summarized in Table 2.

[0093] The photo of the crucible obtained after the reaction product was taken out is shown in the attached figure. Figure 2 As shown in the attached Figure 2 As shown, a large amount of product remains on the crucible wall.

[0094] The oxide solid electrolyte Li obtained in this comparative example 1.3 Al 0.3 Ti 1.7 The yield and appearance status of (PO4)3 are summarized in Table 2:

[0095] Table 1 Relevant process parameters involved in the examples and comparative examples

[0096]

[0097] Table 2 Product yield, appearance and ionic conductivity of each embodiment and comparative example

[0098]

[0099] Combined with Examples 1-6, Comparative Example 1 and Table 1 and Table 2, Figure 1 and 2 It can be seen that the method described in the present invention, that is, applying an organic polymer material containing only C, H and O on the inner wall of a high-temperature calcined reaction vessel to prepare an oxide solid electrolyte can avoid product wall adhesion, improve the yield of the product, and the electrochemical properties of the product are not affected, which is conducive to large-scale commercial production and has high commercial value.

[0100] Combining Example 1, Comparative Example 1 and Example 7, as well as Tables 1 and 2, it can be seen that the oxide solid electrolyte prepared by the method of Example 7 can avoid wall sticking, the product does not expand, and the yield is improved compared with Comparative Example 1, but compared with Example 1, its yield and ion conductivity are both reduced. The reason is that the mass percentage of organic polymer material in the glue prepared in Example 7 is too high, the viscosity of the obtained glue is too high, and the protective layer formed is not only too thick, but also poor in uniformity. Therefore, during the high-temperature calcination process, the reaction raw materials are heated unevenly, affecting the quality and yield of the reaction product. Moreover, due to the excessive thickness of the material, it will cause cost waste, which is not economical.

[0101] In combination with Example 1, Comparative Example 1, Examples 8-9, and Tables 1 and 2, it can be seen that the oxide solid electrolyte prepared by the method of Example 8 and Example 9 has a reduced expansion degree and a significantly improved yield compared with Comparative Example 1, but compared with Example 1, its yield and ionic conductivity are both reduced. The reason is analyzed as follows: the heating rate of Example 8 and Example 9 is too fast or too slow during the high-temperature calcination process. As mentioned above, when the heating rate is too slow, on the one hand, the raw materials in the reaction vessel are heated slowly, reducing the production efficiency, and on the other hand, it is not conducive to the smooth volatilization of the products formed by the decomposition of the colloidal solution in the reaction vessel, thereby affecting the quality and performance of the prepared oxide solid electrolyte; when the heating rate is too fast, the inside of the reaction container is heated unevenly. On the one hand, the reaction of the electrolyte raw materials inside the reaction container will be affected. On the other hand, the protective layer formed by the glue applied to the inner wall of the reaction container is heated unevenly, and then the decomposition and distribution of the glue on the surface of the protective layer are uneven, so that the various parts of the glue protective layer are unevenly stressed, and then the glue may fall off, so that the protective effect of the protective layer is reduced or even has no protective effect.

[0102] The technical features in the claims and / or the specification of the present invention may be combined, and the combination is not limited to the combination obtained by reference in the claims. The technical solution obtained by combining the technical features in the claims and / or the specification is also within the protection scope of the present invention.

[0103] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A method for preparing an oxide solid electrolyte, characterized in that: It includes the following steps: 1) Applying glue on the inner wall of the high-temperature reactor to form a protective layer; the glue is an aqueous solution of a water-soluble polymer material; the polymer material contains only three elements: C, H and O; 2) Putting the precursor powder of the oxide solid electrolyte into a high-temperature reactor containing a protective layer, heating it to a calcination temperature, and keeping it warm at the calcination temperature to allow the precursor powder of the oxide solid electrolyte to react; cooling it after the reaction is completed to obtain an oxide solid electrolyte.

2. The preparation method according to claim 1, characterized in that: The polymer material is selected from at least one of polyethylene oxide, polyethylene glycol, polyvinyl alcohol and starch.

3. The preparation method according to claim 1, characterized in that: The viscosity of the glue is 500-10000 mPa.s.

4. The preparation method according to claim 1, characterized in that: The glue solution is prepared according to the following steps: adding the polymer material into water and stirring it to completely dissolve it to obtain the glue solution; wherein, in terms of mass percentage, the glue solution includes 1-20% of the polymer material and 80-99% of water; the sum of the mass percentages of the polymer material and the water is 100%.

5. The preparation method according to claim 1, characterized in that: The thickness of the protective layer is 0.5-5 mm.

6. The preparation method according to claim 1, characterized in that: The oxide solid electrolyte is a garnet-type structure, a NASICON-type solid electrolyte or a perovskite-type solid electrolyte.

7. The preparation method according to claim 1, characterized in that: The high temperature reactor is an alumina crucible or a zirconia crucible.

8. The preparation method according to claim 1, characterized in that: The heating rate of the heating is 1 to 5°C / min.

9. The preparation method according to claim 1, characterized in that: The calcination temperature is 500-1200°C.

10. The preparation method according to claim 1, characterized in that: The heat preservation time is 2 to 48 hours.